Sedentarism in Recreational Marathon Runners - Nikolaidis PT; Knechtle B (Dove Medical Press, 2023)
Pantelis T Nikolaidis,1,2 Beat Knechtle3,4 1School of Health and Caring Sciences, University of West Attica, Egaleo, Greece; 2Exercise Physiology Laboratory, Nikaia, Greece; 3Institute of Primary Care, University of Zurich, Zurich, Switzerland; 4Medbase St. Gallen am Vadianplatz, St. Gallen, SwitzerlandCorrespondence: Pantelis T Nikolaidis, School of Health and Caring Sciences, University of West Attica, Ag. Spyridonos, Egaleo, 12243, Greece, Tel +30 6977820298, Email pademil@hotmail.comAim: Although it has been previously observed that sedentary behavior (SB) was not related to training duration in marathon runners, little information existed about the relationship of SB with training, anthropometric and physiological characteristics in this population. This study aimed to investigate the prevalence of SB and its correlation with performance parameters (such as body fat percentage, maximal oxygen uptake and weekly training volume) as well as its variation by sex and day (ie, weekdays versus weekend) in recreational marathon runners.Methods: A total of 151 finishers (women, n = 29; men, n = 122; age 43.1 (8.7) years, mean (standard deviation)) in the Athens marathon 2017 performed a series of anthropometric and physiological tests, and completed the Multi-context sitting time questionnaire.Results: SB did not correlate with anthropometric and physiological characteristics and no difference in these characteristics was shown between low and high sedentary participants (p > 0.05). SB did not differ between women and men (p > 0.05), but differed between working and non-working days (p < 0.05).Conclusion: In contrast to previous findings on the general population indicating an association of a high SB with a low cardiorespiratory and muscular fitness, our finding of no correlation between SB and physical fitness in marathon runners suggested that endurance exercise might offset the negative effects of SB.Keywords: body fat, endurance exercise, long distance running, maximal oxygen uptake, moderate exercise intensity, physical inactivity